Differences in livelihood satisfaction between ethnic groups after selling farmland for renewable energy power projects in Ninh Thuan province, Vietnam - Nguyen Ngoc Quang (Frontiers in Sustainable Food Systems)
This study investigated the factors affecting livelihood satisfaction and the differences between ethnic groups after selling farmland for renewable energy power projects in the Ninh Thuan province of Vietnam. Quantitative data were collected through direct questionnaires from 294 households selling land. Factor analysis and related tests were conducted to refine the scale and test the model, and structural equation modeling was conducted to assess the impact of factors on farmers’ livelihood satisfaction and compare the model between the Kinh and ethnic minority groups. The results showed that for the Kinh, all aspects impact livelihood satisfaction, in which economic-financial capital and natural capital have a stronger impact; for the minority group, natural capital has the strongest impact, and physical capital and social capital have insignificant impacts. This result indicates the need for individual solutions suitable for each group to promote livelihood satisfaction.